2018
DOI: 10.1371/journal.pone.0200607
|View full text |Cite
|
Sign up to set email alerts
|

In Silico evaluation and identification of fungi capable of producing endo-inulinase enzyme

Abstract: The enzyme endo-inulinase hydrolyzes inulin to short chain fructooligosaccharides (FOS) that are potential prebiotics with many health promoting benefits. Although the raw materials for inulin production are inexpensive and readily available, commercial production of FOS from inulin is limited due to inadequate availability of the enzyme source. This study aimed to identify the fungi capable of producing endo-inulinase based on the in silico analysis of proteins retrieved from non-redundant protein sequence da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…Penla1_371227, instead, resulted to be related to fungal endoinulinases, displaying 74.7 and 69.6% identities with Penicillium subrubescens endoinulinase Inu2 and A. niger InuA, respectively. Consistently, the Penla1_371227 sequence reveals the presence of all the conserved motifs and the unique aminoacidic residues described for fungal endoinulinases ( Chikkerur et al, 2018 ; Singh et al, 2020a ; Figure 4 ).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Penla1_371227, instead, resulted to be related to fungal endoinulinases, displaying 74.7 and 69.6% identities with Penicillium subrubescens endoinulinase Inu2 and A. niger InuA, respectively. Consistently, the Penla1_371227 sequence reveals the presence of all the conserved motifs and the unique aminoacidic residues described for fungal endoinulinases ( Chikkerur et al, 2018 ; Singh et al, 2020a ; Figure 4 ).…”
Section: Resultssupporting
confidence: 62%
“…A similar profile was already reported for inulinase production in shake-flask fermentations of many fungal species, i.e., Penicillium sp. ( Rawat et al, 2015b ), Aspergillus fumigatus ( Chikkerur et al, 2018 ), Aspergillus niger ( Mahmoud et al, 2011 ), and Aspergillus tritici ( Singh et al, 2020b ).…”
Section: Resultsmentioning
confidence: 99%
“…Although FOS priming also led to similar sugar dynamics in the apoplast (Figure 10), the inefficiency of disease priming can most probably be explained by the fact that B. cinerea harbors inulinase activity [114], indicating it can use FOS as a food source, further confirmed by our own analysis (Figure 10c). This is different from the case of LOS priming, since fungal fructanases have no affinity towards levan-type substrates [137]. Additionally, in the case of the Venturia/apple pathosystem, inulin proved inefficient in priming as compared to levan, and this could be linked to the fact that the fungus was able to grow on inulin but not on levan [78].…”
Section: Discussionmentioning
confidence: 91%
“…The accuracy of the HFBII protein model was measured using a Ramachandran plot [85] and the result (97.5%) was satisfactory (Figure S1). The PROSA web server was used to analyze the protein structure by matching the predicted with the experimental structures using the statistics of the Cα of the mean force to evaluate the quality of the predicted proteins [86]. The output Z-score plots from the PROSA server revealed that the predicted protein models were within the range of the experimentally determined structures using the NMR method (Figure S2).…”
Section: Modeling Of 3d Protein Structures and Model Evaluationmentioning
confidence: 99%